Using vignettes to improve understanding of Social Security and annuities. (14th July 2022) - Samek, Anya; Kapteyn, Arie; Gray, Andre
Abstract: Evidence shows that people have difficulty understanding complex aspects of retirement planning, which leads them to under-utilize annuities and claim Social Security benefits earlier than is optimal. To target this problem, we developed vignettes about the consequences of different annuitization and claiming decisions. We evaluated our vignettes using an experiment with a representative online panel of nearly 2, 000 Americans. In our experiment, respondents were either assigned to a control group with no vignette, to a written vignette, or to a video vignette. They were then asked to give advice to hypothetical persons on annuitization or Social Security claiming, and were asked factual questions about these concepts. We found evidence that being exposed to vignettes led respondents to give better advice. For example, the gap between advised claim age for a relatively healthy person versus a relatively sick person was larger by nearly a year in the vignette treatments than in the control group. Furthermore, the vignettes increased financial literacy related to these concepts by 10–15 percentage points. Interestingly, the mode of communication did not have a significant impact – the video and written vignettes were equally effective.